2012
DOI: 10.1124/jpet.112.199778
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Mer Receptor Tyrosine Kinase Signaling Attenuated Lipopolysaccharide-Induced Lung Inflammation

Abstract: Mer receptor tyrosine kinase (Mer) signaling plays a central role in the intrinsic inhibition of the inflammatory response to Tolllike receptor activation. Previously, we found that lung Mer protein expression decreased after lipopolysaccharide (LPS) treatment due to enhanced Mer cleavage. The purpose of the present study was to examine whether pharmacologically restored membrane-bound Mer expression upregulates the Mer signaling pathways and suppresses lung inflammatory responses. Pretreatment with the ADAM17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…MerTK engagement triggers AC internalization via cytoskeletal signaling, and it also activates an anti-inflammatory response by suppressing NF-κB (15,16). As such, MerTK knockout mice develop a lupus-like phenotype in aged mice (17), demonstrate accelerated atherosclerosis in hypercholesterolemic mice due to defective clearance of ACs and heightened inflammation (18,19), and have increased peritonitis in response to a sterile inflammatory stimulus (20).…”
Section: -Lipoxygenasementioning
confidence: 99%
“…MerTK engagement triggers AC internalization via cytoskeletal signaling, and it also activates an anti-inflammatory response by suppressing NF-κB (15,16). As such, MerTK knockout mice develop a lupus-like phenotype in aged mice (17), demonstrate accelerated atherosclerosis in hypercholesterolemic mice due to defective clearance of ACs and heightened inflammation (18,19), and have increased peritonitis in response to a sterile inflammatory stimulus (20).…”
Section: -Lipoxygenasementioning
confidence: 99%
“…This hypothesis is supported by previous studies showing that MerTK loss from the mammary gland during physiological postpartum involution reduces efferocytosis of dying MECs, causing impaired upregulation of Il10 and Tgfb1 (30). Other studies demonstrated that MerTK-mediated efferocytosis of dying neutrophils or injured cardiomyocytes, liver cells, or lung epithelial cells induces the transcription of wound-healing cytokines that promote resolution of acute inflammation and tissue repair (47,50,54,(58)(59)(60)(61)(62). While MerTK-mediated efferocytosis is desirable in physiological (e.g., postpartum involution of the breast) or pathological (e.g., tissue damage) wound-healing situations, our results suggest that efferocytosis-mediated tissue repair in tumors would enhance tumor metastasis.…”
Section: Decreased Wound-healing Cytokines In Postpartum Mertkmentioning
confidence: 99%
“…Although advances in supportive care and ventilator management for human ARDS have reduced short-term mortality [2], effective pharmacological therapies are still lacking. In this context, recent studies evaluated the role of tyrosine kinase inhibitors in experimental ARDS [3][4][5]. As major therapeutic agents in oncology, these pharmacological agents block the action of different classes of protein tyrosine kinases (PTKs), important molecules that regulate many intracellular signaling pathways, including the acute inflammatory response to different stimuli [6].…”
Section: Introductionmentioning
confidence: 99%